Factibilidad económica de la producción del cultivo de pitahaya (stenocereus thurberi) en el Cantón Ventanas Provincia de Los Ríos, año 2015. - Aguirre Cerezo, Kevin Steven (2016)
This research concerns the "economic feasibility of crop production pitaya (Stenocereus Thurberi) in the canton Ventanas Los Rios Province, 2015" in which several objectives that wish to carry out a market study developed and the assessment of investment and production costs of cultivation, to thereby determine the economic benefit generated dragon fruit cultivation. research was based through the conceptual framework that theoretically contributed to its scientific basis on the theories of production, different types of research, proper financial processes for determining the profitability of the project, all these livelihoods posed warrant investigation . Within the market study it was found that the production of the crop of dragon fruit in the canton Windows does not have enough host since being agricultural and considered the corn capital of Ecuador area, the first crop of the area is properly corn, soybeans among others. For the above it is relevant to assess whether this crop is profitable for farmers to have other options and to diversify crops that offers new alternatives and thus conducive to improving their living conditions. As part of other objectives the value of the investment for this project was $ 23,998 (twenty two thousand nine hundred ninety-eight US dollars) and the costs of crop production pitahaya were for the first year of $ 9.804,90 was considered ( nine thousand eight hundred and four US dollars and ninety cents), for the second year worth $ 8,295.00 (eight thousand two hundred ninety-five US dollars) and for the year of harvest for this crop is his third year was $ 12.678,75 (twelve thousand six hundred seventy-eight US dollars and seventy five cents) With the data obtained in the investigation it was determined that the cost benefit of it is that for $ 1.98 (one dollar and ninety eight cents) which means that for every dollar invested the company has $ 0.98 (ninety eight cents) which is highly profitable.